Stem Cell Therapy for Pediatric Traumatic Brain Injury - Lengel, Dana; Sevilla, Cruz; Romm, Zoe L.; Huh, Jimmy W.; Raghupathi, Ramesh (Frontiers in Neurology, 2020)
There has been a growing interest in the potential of stem cell transplantation as therapy for pediatric brain injuries. Studies in pre-clinical models of pediatric brain injury such as Traumatic Brain Injury (TBI) and neonatal hypoxia-ischemia (HI) have contributed to our understanding of the roles of endogenous stem cells in repair processes and functional recovery following brain injury, and the effects of exogenous stem cell transplantation on recovery from brain injury. Although only a handful of studies have evaluated these effects in models of pediatric TBI, many studies have evaluated stem cell transplantation therapy in models of neonatal HI which has a considerable overlap of injury pathology with pediatric TBI. In this review, we have summarized data on the effects of stem cell treatments on histopathological and functional outcomes in models of pediatric brain injury. Importantly, we have outlined evidence supporting the potential for stem cell transplantation to mitigate pathology of pediatric TBI including neuroinflammation and white matter injury, and challenges that will need to be addressed to incorporate these therapies to improve functional outcomes following pediatric TBI.